Managing service in food and beverage operations - Moore, Charlotte (States Academic Press, 2021)
Food and beverage operations refer to those industrial processes which are used in the preparation and distribution of food for commercial purposes. Some of the common examples of food service industry are restaurants, cafeterias, catering services, etc. The companies involved in these activities are called food service distributors. These distributors undertake a variety of operations such as menu planning, food storage, transportation and restaurant management. Food safety and preservation is an important aspect of this industry. Chilling, freezing, salting, canning, smoking and dehydration are frequently used by food service providers to increase the longevity of food. The book aims to shed light on some of the unexplored aspects of food and beverage operations. It outlines the processes and applications related to this field. Those in search of information to further their knowledge will be greatly assisted by this book.